Recent developments in nanocarriers for cancer chemotherapy - Debabrata Ghosh Dastidar; Dipanjan Ghosh; Amlan Das (OpenNano, 2022)
Cancer is caused due to the unregulated proliferation of cells. Understanding the differences between a cancer cell and a normal cell; a normal tissue and a tumor microenvironment is the key to developing an efficient targeted drug delivery system for cancer therapy. With recent developments in cancer cell biology, materials science, and nanotechnology a lot of new strategies have been established for active tumor-targeted drug delivery. With the help of nanocarriers, it is now possible to deliver the optimum dose of combinations of anticancer drugs specifically within the cytoplasm of cancer cells. In addition, inorganic and organic self-therapeutic nanomaterials have been developed. They are nanoparticles made up of materials with anticancer activity. This review article elaborates on the barriers in cancer therapy and the recent developments to overcome those barriers with different modern nanocarriers and self-therapeutic nanomaterials.